Optical Techniques for Information Security - Matoba, Osamu; Nomura, Takanori; Perez-Cabre, Elisabet; Millan, MarÍa S.; Javidi, Bahram (Proceedings of the IEEE, 2009)
This paper presents an overview of the potential of free space optical technology in information security, encryption, and authentication. Optical waveform posses many degrees of freedom such as amplitude, phase, polarization, spectral content, and multiplexing which can be combined in different ways to make the information encoding more secure. This paper reviews optical techniques for encryption and security of two-dimensional and three-dimensional data. Interferometric methods are used to record and retrieve data by either optical or digital holography for security applications. Digital holograms are widely used in recording and processing three dimensional data, and are attractive for securing three dimensional data. Also, we review optical authentication techniques applied to ID tags with visible and near infrared imaging. A variety of images and signatures, including biometrics, random codes, and primary images can be combined in an optical ID tag for security and authentication.